Iodine‐Promoted Oxidative Amidation of Terminal Alkenes – Synthesis of α‐Ketoamides, Benzothiazoles, and Quinazolines1. Issue 7 (27th January 2015) - Deshidi, Ramesh; Devari, Shekaraiah; Shah, Bhahwal Ali
Abstract: A novel metal‐free strategy for oxidative amidation of terminal alkenes by using I2 /DMSO for the synthesis of α‐ketoamides has been developed. Intriguingly, the use of tert ‐butylhydroperoxide (TBHP) as co‐oxidant can facilitate the synthesis of α‐ketoamides at room temperature without any solvent, thereby making it a green protocol. The reaction with primary amines can be easily achieved by using SeO2 as an oxidizing agent. Besides, the scope of the method was also extended to the synthesis of benzothiazolines and quinazolines. Abstract : A novel metal‐free strategy for oxidative amidation of terminal alkenes using I2 /DMSO for the synthesis of α‐ketoamides has been developed. Intriguingly, the use of tert ‐butylhydroperoxide (TBHP) as co‐oxidant can facilitate the synthesis of α‐ketoamides at room temperature without any solvent, whereas for reaction with primary amines SeO2 is required as oxidizing agent.